Pharmacogenomic polygenic response score predicts ischaemic events and cardiovascular mortality in clopidogrel-treated patients. Issue 4 (3rd September 2019) - Lewis, Joshua P; Backman, Joshua D; Reny, Jean-Luc; Bergmeijer, Thomas O; Mitchell, Braxton D; Ritchie, Marylyn D; Déry, Jean-Pierre; Pakyz, Ruth E; Gong, Li; Ryan, Kathleen; Kim, Eun-Young; Aradi, Daniel; et al.
Abstract: Aims : Clopidogrel is prescribed for the prevention of atherothrombotic events. While investigations have identified genetic determinants of inter-individual variability in on-treatment platelet inhibition (e.g. CYP2C19 *2), evidence that these variants have clinical utility to predict major adverse cardiovascular events (CVEs) remains controversial. Methods and results : We assessed the impact of 31 candidate gene polymorphisms on adenosine diphosphate (ADP)-stimulated platelet reactivity in 3391 clopidogrel-treated coronary artery disease patients of the International Clopidogrel Pharmacogenomics Consortium (ICPC). The influence of these polymorphisms on CVEs was tested in 2134 ICPC patients ( N  = 129 events) in whom clinical event data were available. Several variants were associated with on-treatment ADP-stimulated platelet reactivity ( CYP2C19 *2, P  = 8.8 × 10 −54 ; CES1 G143E, P  = 1.3 × 10 −16 ; CYP2C19 *17, P  = 9.5 × 10 −10 ; CYP2B6 1294 + 53 C > T, P  = 3.0 × 10 −4 ; CYP2B6 516 G > T, P  = 1.0 × 10 −3 ; CYP2C9 *2, P  = 1.2 × 10 −3 ; and CYP2C9 *3, P  = 1.5 × 10 −3 ). While no individual variant was associated with CVEs, generation of a pharmacogenomic polygenic response score (PgxRS) revealed that patients who carried a greater number of alleles that associated with increased on-treatment platelet reactivity were more likely to experience CVEs (β = 0.17, SE 0.06, P  = 0.01) and cardiovascular-related death (β = 0.43, SE 0.16, P  = 0.007). Patients who carried eight or more risk alleles were significantly more likely to experience CVEs [odds ratio (OR) = 1.78, 95% confidence interval (CI) 1.14–2.76, P  = 0.01] and cardiovascular death (OR = 4.39, 95% CI 1.35–14.27, P  = 0.01) compared to patients who carried six or fewer of these alleles. Conclusion : Several polymorphisms impact clopidogrel response and PgxRS is a predictor of cardiovascular outcomes. Additional investigations that identify novel determinants of clopidogrel response and validating polygenic models may facilitate future precision medicine strategies.